2013
DOI: 10.1371/journal.pone.0084108
|View full text |Cite
|
Sign up to set email alerts
|

The PHA Test as an Indicator of Phagocytic Activity in a Passerine Bird

Abstract: Several techniques in ecological immunology have been used to assess bird immunocompetence thus providing useful information to understand the contribution of the immunological system in life-history decisions. The phytohaemagglutinin (PHA)-skin test has been the most widely employed technique being interpreted as the sole result of T lymphocytes proliferation and hence used to evaluate acquired immunological capacity. However, the presence of high numbers of phagocytic cells in the swelling point has cast som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 60 publications
(91 reference statements)
1
32
1
1
Order By: Relevance
“…In contrast to the BKAs, PHA injection may measure both subsets of the immune system. The primary PHA injection mainly measures the pro-inflammatory, phagocytic potential of the innate immune system, whilst the swelling from subsequent injections may provide insight into acquired immunity via immunologic memory (Finger et al, 2013;Martin et al, 2006;Salaberria et al, 2013;Vinkler et al, 2010). Unexpectedly and contrary to our previous findings (Finger et al, 2013), the animals used herein showed no immunologic memory (i.e., subsequent injections did not increase swelling) although there was a significant effect of sampling implying an age and/or seasonal response to antigenic injection.…”
Section: Phacontrasting
confidence: 79%
“…In contrast to the BKAs, PHA injection may measure both subsets of the immune system. The primary PHA injection mainly measures the pro-inflammatory, phagocytic potential of the innate immune system, whilst the swelling from subsequent injections may provide insight into acquired immunity via immunologic memory (Finger et al, 2013;Martin et al, 2006;Salaberria et al, 2013;Vinkler et al, 2010). Unexpectedly and contrary to our previous findings (Finger et al, 2013), the animals used herein showed no immunologic memory (i.e., subsequent injections did not increase swelling) although there was a significant effect of sampling implying an age and/or seasonal response to antigenic injection.…”
Section: Phacontrasting
confidence: 79%
“…Salaberria et al . ). In our study, no differences in proteins between the two different challenges were noticed, but the PHA response was significantly correlated with plasma protein levels, highlighting the innate components of the immune response.…”
Section: Discussionmentioning
confidence: 97%
“…These common results in males could be interpreted on the light of common components in the innate and adaptive axes of the immune system (Forsman et al 2010;Vinkler et al 2010). In fact, some studies have shown that the PHA swelling response is an integration of both specific and induced immunity and also of constitutive and nonspecific immunity (Martin et al 2006a;Salaberria et al 2013). However, contrary to lysozyme activity, CMI was also influenced by several variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to directly compare those patterns with those reported here because here we have used a measure of the external swelling response, which involves not only proliferation of T-cells but also the secretion of proinflammatory cytokines that recruit and activate effector cells and phagocytes such as basophils, heterophils, and macrophages (Martin et al 2006a;Salaberria et al 2013) and thus involves both innate and adaptive components of the immune system (Stadecker et al 1977;Bílková et al 2015).…”
Section: Discussionmentioning
confidence: 99%